Peran Financial self efficacy memoderasi Literasi Keuangan dan Fintech Payment, Terhadap Perilaku Manajemen Keuangan - Fitri Susilowati; Nabila Alfi Rizqina (JURNAL ILMIAH MANAJEMEN & BISNIS, 2026)
Purpose – This study aims to examine the influence of financial literacy, fintech payments, and internal locus of control on financial management behaviour, with financial self-efficacy as a moderating variable, in a study of Generation Z in Java.Methodology – This study used a quantitative approach. Data were obtained from 240 Generation Z individuals in Java through questionnaires and analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS). The analysis was conducted to test the direct relationship between the variables and the moderating effect of financial self-efficacy.Findings – The results show that financial literacy and fintech payments have a significant positive effect on financial management behaviour, while internal locus of control has no effect. Financial self-efficacy moderates the influence of fintech payments on financial management behaviour, but does not moderate the influence of financial literacy and internal locus of control on financial management behaviour.Originality – This study contributes by partially examining the influence of financial literacy, fintech payments, and internal locus of control on financial management behaviour, while also positioning financial self-efficacy as a moderating variable. This study expands the literature on financial management behaviour by adding a limited moderating perspectiveImplications – These findings emphasise the need to maintain and direct financial literacy to maintain sound financial behaviour and management. Furthermore, the significant influence of financial self-efficacy on the relationship between fintech payments and financial management behaviour indicates that it plays a crucial role in regulating fintech payment use. With strong financial self-efficacy, Generation Z can utilise fintech payments as a financial management tool.